Mobile user location Prediction in cellular network using Agent Technique - Shanmugarthinam, G (International Journal of Computer Sciences and Engineering, 2025)
In mobile computing to determine the future location of Mobile user movement is used to manage communication and to provide the Quality of location based services. Mobile computing surroundings are considered by wireless links are not faster and comparatively below privileged hosts are battery powers were inadequate , inclined to frequent interruptions. Mobile hosts (MHs) caching a data in a wireless network helps to slove the problems related with slow, inadequate bandwidth wireless links, by plummeting preserving bandwidth. Battery power is preserved by plummeting the number of up-link requests. There are some problems due to incomplete wireless communication, partial client source, suspension of client and unobstructed mobility. So it is problematic to uphold the data cache and pre-fetch in mobile computing. Three key techniques, namely, FLA (Future Location Agent), PLA (Preceding Location agent) and CLA (Contemporary Location agent) have been designed and proposed the future mobile user location using the user movement history. These methods use log and thread harmonization Classical for data caching and prefetching conservation in site founded queries .This method consequences in abridged server workload saving of wireless bandwidth and abridged network traffic.